An Ultra-High Temperature Stable Solar Absorber Using the ZrC-Based Cermets - Wang, Jian; Wu, Zuoxu; Liu, Yijie; Hou, Shuaihang; Ren, Zhikun; Luo, Yi; Liu, Xingjun; Mao, Jun; Zhang, Qian; Cao, Feng (Frontiers in Energy Research, 2021)
Exploring the spectrally selective absorbers with high optical performance and excellent thermal stability is crucial to improve the conversion efficiency of solar energy to electricity in concentrated solar power (CSP) systems. However, there are limited reports on the selective solar absorbers utilized at 900 oC or above. Herein, we developed a selective absorption coating based on the ultra-high temperature ceramic ZrC and the quasi-optical microcavity (QOM) optical structure, and experimentally achieved the absorber via depositing an all-ceramic multilayer films on a stainless steel substrate by magnetron sputtering. The prepared multi-layer selective absorber demonstrates an excellent high solar absorptance of ~0.964 due to the multi absorptance mechanisms in the QOM, and a relatively low thermal emittance of ~0.16 (82 ℃). Moreover, the coating can survive at 900 oC in vacuum for 100 h with a superior spectral selectivity of 0.96/0.143 (82 ℃) upon annealing, resulting from the introduction of ultra-high temperature ceramic ZrC in the QOM structure. Under the conditions of a stable operating temperature of 900 ℃ and a concentration ratio of 1000 suns, the calculated ideal conversion efficiency using this absorber can reach around 68%, exceeding most solar selective absorbers in previous reports.